Supporting Factors, Inhibiting Factors, and Opportunities for Islamic Financial Institutions in the Global Economy - Muhamad Mujib; Muhammad Faishol (Journal of Business Improvement, 2024)
The establishment of various Sharia financial institutions and the issuance of Sharia-based financial instruments marked the development of the Sharia financial system. Shariah financial institutions were established to promote and develop Islamic principles. They have roles in the world economy, especially the economy of a country, which can help the community, such as providing financial services, promoting economic progress, carrying out social activities, well-being, and economic justice. To reach the expected conclusions and results, this study uses a type of descriptive qualitative research with data collection techniques using library studies. With a population of over 270 million, a Muslim majority, and Islamic economic potential, especially Shariah finance, Indonesia is still seen as a country with great potential for prosperity